National security-related foreign investment screening laws and investment efficiency - Godsell, David (Review of Accounting Studies, 2026)
Abstract This study investigates the effect of national security-related foreign investment screening laws on managers’ investment choices. These laws weaken takeover markets by granting regulators broad new powers to revise or reject foreign takeovers of firms in national security-related industries. I identify exogenous variation in national security-related foreign investment screening laws using the enactment of a U.S. national security-related foreign investment screening law known as the Foreign Investment and National Security Act (FINSA). Consistent with managerial entrenchment theory, I document that, following the enactment of FINSA, national security firms’ inefficient investment increases. Event-time tests corroborate and cross-sectional tests demonstrate that results strengthen with treatment strength. Results generalize to seven alternative investment efficiency measures. Stacked panel tests exploiting regulators’ staggered enforcement of FINSA across 66 industries over time between 2008 and 2021 further corroborate. Overall, this study documents the unintended consequences of national security-related foreign investment screening laws on managers’ investment choices.